LONG-TERM VISUAL OUTCOMES AND CLINICAL FEATURES AFTER ANTI–VASCULAR ENDOTHELIAL GROWTH FACTOR INJECTION–RELATED ENDOPHTHALMITIS. Issue 11 (November 2019) - Rayess, Nadim; Obeid, Anthony; Storey, Philip P.; Juliano, Joseph; Rahimy, Ehsan; Moshfeghi, Andrew A.; Garg, Sunir; Hsu, Jason
Abstract : Purpose: To determine long-term visual outcomes in patients who developed endophthalmitis after intravitreal anti–vascular endothelial growth factor injections and to correlate visual outcomes with clinical features. Methods: This is a retrospective, multicenter, consecutive case series of patients diagnosed with anti–vascular endothelial growth factor injection–related endophthalmitis who were treated at Mid Atlantic Retina, the Retina Service of Wills Eye Hospital, Philadelphia, PA, and the University of Southern California Roski Eye Institute, Los Angeles, CA. Patients were included if they had at least 1 year of follow-up. Primary outcome was to evaluate long-term visual outcomes up to 5 years of follow-up. The secondary outcome was to determine clinical features (e.g., culture results) that may predict long-term visual acuity outcomes. Results: A total of 56 cases of endophthalmitis from 168, 247 anti–vascular endothelial growth factor injections were identified (0.033%, 1/3, 004 injections), from which 51 eyes met inclusion criteria. Mean follow-up period was 3.3 years (median 4 years; range 1–5 years). A total of 24 patients (47%) reached a maximum final follow-up of 5 years. Mean Snellen visual acuity at the causative injection visit was 20/102 and decreased to counting fingers at diagnosis ( P < 0.001). At 6-month follow-up, mean visual acuity improved to 20/644 ( P < 0.001) and remained stable up to 5 years (20/480, P = 0.003) follow-up compared with diagnosis. At the final follow-up, 20 eyes had visual acuity that returned to within one line of baseline visual acuity (visual recovery group), whereas 31 patients' visual acuity was at least one line worse than initial visual acuity (visual deterioration group). The cultures for the visual recovery group were more likely to grow coagulase-negative Staphylococcus, whereas the visual deterioration group primarily grew Streptococcus species, Staphylococcus aureus, and Enterococcus faecalis ( P = 0.002, comparing organisms isolated in the visual recovery and deterioration group). Conclusion: Visual outcomes after anti–vascular endothelial growth factor injection–related endophthalmitis seem to reach peak improvement by 6 months and remain stable up to a median of 4-year follow-up. Patients who develop culture-negative endophthalmitis or endophthalmitis secondary to coagulase-negative Staphylococcus are more likely to regain baseline visual acuity compared with cases secondary to Streptococcus species . Abstract : This multicenter study evaluates long-term visual outcomes and clinical features that may predict visual recovery or deterioration in patients who develop endophthalmitis after anti–vascular endothelial growth factor injections. The authors' results demonstrate that visual outcomes reach a peak at 6 months and remain stable for up to 5 years of follow-up.